Subscribers' expectations of internet speed for multiplayer online battle arena (MOBA) game - Naknawa, Manus; Ibrahim, Adamu Abubakar (IIUM Press, 2021)
Internet bandwidth is crucial for many businesses and applications related to people's social and commercial activities in this current generation. This research examines the factors influencing Internet bandwidth service's fluctuation on unlimited Internet plans from four Internet Service Providers (ISP) companies in Malaysia (Umobile, Hotlink, Yes 4G, Xpax). The research's motivation lies with the fact that whether ISPs were really providing what they are advertising, or there is a need for expressing doubt on the maximum bandwidth users pay for and can actually get those bandwidths or not. Based on this issue, this research proposes an experimental analysis to investigate the factors influencing the fluctuation of Internet bandwidth when using a Multiplayer online battle arena (MOBA) game because it is a huge bandwidth-demanding game. The MOBA game selected for this particular study is Dota 2. Different simulation scenarios were formulated to measure latency, packet loss, and traffic used to identify the factors of fluctuating bandwidth usage. A PowerShell is used for determining those attributes, while in-game monitoring and cFosspeed are also used for tracking bandwidth and real-time ping, packet loss. The actual bandwidth measure was conducted with the Ookla application for testing the bandwidth. The simulation scenarios were undertaking for a round-period of time but at the same location for all the SIMs. After 30 minutes of simulation, the results indicate that Xpax is the best among ISP companies in terms of latency, bandwidth usage, traffic used, and player’s experience. Still, for the packet loss, Hotlink and Yes 4G performed better. Umobile failed to stay 30 minutes of the simulation due to a connection problem and cannot reconnect. For the actual bandwidth test, the results indicate that the time (Peak, Off-Peak) a user accesses the internet has affected the maximum bandwidth for some ISP companies (e.g., Hotlink). The research findings reveal that an actual bandwidth result depends on location and congestion indicated by the signal bar. Moreover, the simulation found out that ping is the main factor for bandwidth usage while playing the MOBA game. If there is a ping spiking scenario, the bandwidth will use more than usual, more or less is dependent on how severe occurrences of spiking scenario. The finding concluded that Ping spikes and lag spikes in-game are ISP issues and are the factors influencing the fluctuation of internet bandwidth service for MOBA games